Strategi Integrasi Pendidikan Agama Islam dan Pendidikan Karakter untuk Meningkatkan Moralitas Siswa - Siti Munajah (PT Barkah Ilmi Fiddunya, 2024)
The integration of Islamic Religious Education (PAI) and character education is a holistic approach to the learning process which aims to develop students comprehensively, both from a spiritual and moral perspective. This research aims to examine the implementation of integration between PAI and educational character in educational institutions. PAI offers fundamental values ​​such as honesty, responsibility and empathy, which are in line with the goals of character education. In this context, the educational curriculum can be enriched by integrating Islamic principles in every aspect of teaching, both in religious subjects and general subjects. Models of exemplary behavior from educators, supportive extracurricular activities, and the application of case study-based teaching methods are important tools in facilitating students to understand and apply religious values ​​in everyday life. Dialogue and reflection also play a central role in this process, allowing students to think about and internalize religious teachings and character values. This approach aims to form individuals who not only excel academically, but also have strong character and noble character, ready to face social challenges with high responsibility and ethics.